2017
DOI: 10.4049/jimmunol.1601991
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Disruption of CD4 and CD8 Genes Facilitates the Development of Double Negative αβ TCR+ Peripheral T Cells That Respond Robustly to Staphylococcal Superantigen

Abstract: Mature peripheral double negative (DN) T cells expressing αβ TCR but lacking CD4/CD8 co-receptors play protective as well as pathogenic roles. To better understand their development and functioning in vivo, we concomitantly inactivated CD4 and CD8 genes in mice with intact MHC class I and class II molecules with the hypothesis that this would enable the development of DNT cells. We also envisaged that these DNT cells could be activated by bacterial superantigens in vivo as activation of T cells by superantigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…This shows that αβ T cells that recognize Ags apart from pMHC can be positively selected if Lck is not sequestrated by CD4 or CD8. Importantly the numbers of thymic and peripheral γδ T cells are unaffected in CD4 and CD8 double KO mice . The independence of γδ T cells from CD4 and CD8 might be reflected in the different architecture of the γδ TCR compared to the αβ TCR.…”
Section: Ligand Recognition By αβ and γδ Tcrsmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that αβ T cells that recognize Ags apart from pMHC can be positively selected if Lck is not sequestrated by CD4 or CD8. Importantly the numbers of thymic and peripheral γδ T cells are unaffected in CD4 and CD8 double KO mice . The independence of γδ T cells from CD4 and CD8 might be reflected in the different architecture of the γδ TCR compared to the αβ TCR.…”
Section: Ligand Recognition By αβ and γδ Tcrsmentioning
confidence: 99%
“…Importantly the numbers of thymic and peripheral 𝛾𝛿 T cells are unaffected in CD4 and CD8 double KO mice. 36 The independence of 𝛾𝛿 T cells from CD4 and CD8 might be reflected in the different architecture of the 𝛾𝛿 TCR compared to the 𝛼𝛽 TCR. It has been shown that the conserved TCR-𝛼 CP is important for the interaction of murine 𝛼𝛽 TCRs with CD8.…”
Section: Ligand Recognition By 𝜶𝜷 and 𝜸𝜹 Tcrsmentioning
confidence: 99%
“…DNT cells could express perforin, granzyme B and FasL to suppress CD4 + , CD8 + T cells’, B cells’, dendritic cells’ and NK cells’ activity [ 22 ], thus protecting the allograft against rejection in organ transplantation [ 6 , 23 , 24 , 25 , 26 , 27 , 28 ]. Strategies using adoptive transfer of DNT cells also prevented the development of graft versus host disease (GVHD) and autoimmune diseases [ 29 , 30 , 31 ]. DNT cells are also an important T cell population in the liver and kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike many receptors that are internalized after continuous stimulation, the CD4 molecule present on the surface of CD4 + T cells do not disappear via internalization ( 11 ). A recent study reported that concomitant disruption of the CD4 and CD8 genes facilitated the development of DNT cells in the periphery ( 25 ). This study used transgenic mice expressing human HLA class II molecules, HLA-DR3 or HLA-DQ8, as test subjects.…”
Section: Discussionmentioning
confidence: 99%